A vinculação das grandes corporações econômicas empresariais aos direitos fundamentais - Antunes, Euzébio Henzel (2014)
The present work has the objective of, primarily, bring some considerations about the effectiveness of fundamental rights in the context of individual and social rights in relations between individuals and big enterprise business corporations. It examines legal principles involved in the subject, such as the unity of the legal system, the human dignity, the equality and solidarity, and the necessary relativity of autonomy so that there is effectively protection of the fundamental rights. It approaches about some theories on the effectiveness of fundamental rights in private relations, especially the theory of direct or immediate effectiveness, and the theory of indirect or mediate effectiveness. It asks about the mode and intensity of the vinculation of these entities, analyzing substantive criteria to be used in the judgment (analisys of values involved in the solution of concrete cases), in special the criterion of the social function of the company and the contract, becoming some considerations on the fundamental duties in the implementation of fundamental rights. For the last, we analyze homelands jurisprudence on the application of the effectiveness of the fundamental rights of individuals and big enterprise business corporations. It is inferred that the theory to be applied to the cases, in principle, is the theory of immediate effectiveness, with the establishment of canons by which this binding should occur (to what extent). This work has the objective of demonstrating the direct linking of big enterprise business corporations to fundamental rights, analysing specific aspects of the subject, as well as providing information and study by the law operators about current and relevant topic.